Impact of Bushmeat Hunting on Wild Animal's Biomass in the Western Indian Himalaya - Hilaluddin (Indian Forester, 2017)
The impacts of bushmeat hunting on wild animal biomass were examined in the western Indian Himalaya. Ungulates and pheasants metabolic biomass were generally higher in protected sites as compared to hunted sites. In protected site, ungulates had the greatest metabolic biomass whereas pheasants the least. Koklass pheasant (Pucrasia macrolopha) and Kaleej pheasant (Lophura leucomelanos) have shown statistically significant variations for their biomass in hunted and protected sites, whereas densities of Cheer pheasant (Catreus wallichi) and Monal pheasant (Lophophorus impejanus) did not show statistically significant differences between the two management units. The biomass of Barking deer (Muntiacus muntijak), Himalayan tahr (Hemitragus jemlahicus) and Serow (Capricornis sumatraensis) were significantly higher in protected site as compared to hunted site, whereas Goral (Nemorhaedus goral) biomass between the two types of forest patches statistically remained similar.